TINJAUAN YURIDIS TERHADAP PASAL 27 AYAT (1) UNDANG – UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Kartika Agus Salim (Universitas Kapuas Sintang, 2019)
Abstract Prohibited acts are intentionally and without the right to distribute and / or transmit and / or make accessible electronic information and / or electronic documents that have contents that violate decency. Seeing the legal facts that occur on the internet the creators of these sites should be arrested by the authorities to account for their actions for violating the law on Information and Electronic Transactions and the Pornography Act. The crime committed by the makers of these immoral sites has made people who watch and see pornographic images and videos make a desire to do. The method of approach used by the author is the normative juridical (literature) approach to primary, secondary and tertiary legal materials. The nature of the research in this study is the normative juridical approach. Normative Legal Approach is a process to find the rule of law, legal principles, and legal doctrines in order to answer the legal issues faced in order to produce new arguments, theories and concepts as a prescription in solving the problems faced. The results of this study indicate that the Electronic Information and Transaction Law is a law made to follow up on the use of the internet and information technology as a means of transacting and communicating electronically. In the law there are still many things that need to be added, especially in accordance with the paragraphs to consider the letter “e” namely that the use of Information Technology plays an important role in trade and national economic growth to realize the welfare of society and the second purpose of the principles and objectives of the Information and Transaction Law Electronics namely “developing national trade and economy in order to improve people’s welfare”. Article 27 Paragraph (1) The Information and Electronic Transaction Act of 2008 does not provide an explanation of what is meant by being accessible, transmitting, and the definition of decency is not explained by the definition of decency which is interpreted according to the criminal law (KUHP). Keywords: Review, Juridical, Information, electronic transactions.